A simulation model for outpatient appointment scheduling with patient unpunctuality. (2016) - Luo, Li; Zhou, Ying; Han, Bernard T.; Shi, Yingkang; Song, Qiyun; He, Xiaoli; Guo, Zhaoxia
This paper is to investigate the appointment system of an outpatient department in a large hospital in China in order to reduce its long patient waiting time. Through a sensitivity analysis using actual data, the study shows that patient unpunctuality and doctor consultation time have significant impacts on the patient waiting time. To facilitate the existing practice without making strong assumptions, a simulation model is developed to identify proper appointment rules for appointment scheduling with severe patient unpunctuality. In specific, four outpatient environments, characterised by a preset appointment time interval with variable doctor consultation times, were simulated and 100 scenarios were run for each environment to identify a proper appointment rule that has the least patient average waiting time (PAWT). Results indicate that PAWT is consistently shorter for environments when patients are punctual and, moreover, is barely affected by the length of appointment time interval. However, for environments with patient unpunctuality, a proper appointment rule could potentially reduce PAWT up to 34% (i.e., reducing the appointment time interval from 1.0 hour to 0.5 hour). The developed simulation model may serve as an efficient tool to enhance outpatient appointment scheduling with patient unpunctuality. Possible extensions to the presented model are also discussed.